2014
DOI: 10.1111/mmi.12826
|View full text |Cite
|
Sign up to set email alerts
|

Localisation and interactions of the Vipp1 protein in cyanobacteria

Abstract: The Vipp1 protein is essential in cyanobacteria and chloroplasts for the maintenance of photosynthetic function and thylakoid membrane architecture. To investigate its mode of action we generated strains of the cyanobacteria Synechocystis sp. PCC6803 and Synechococcus sp. PCC7942 in which Vipp1 was tagged with green fluorescent protein at the C-terminus and expressed from the native chromosomal locus. There was little perturbation of function. Live-cell fluorescence imaging shows dramatic relocalisation of Vip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 53 publications
4
88
2
Order By: Relevance
“…2). Such a pattern of GFP localization is not observed in cells expressing free GFP, or in cells expressing other GFP-tagged proteins associated with the cytoplasmic membrane (Bryan et al, 2014). This indicates that the crescent-like distribution reflects a specific aspect of PilB1 behaviour.…”
Section: N Schuergers and Othersmentioning
confidence: 90%
“…2). Such a pattern of GFP localization is not observed in cells expressing free GFP, or in cells expressing other GFP-tagged proteins associated with the cytoplasmic membrane (Bryan et al, 2014). This indicates that the crescent-like distribution reflects a specific aspect of PilB1 behaviour.…”
Section: N Schuergers and Othersmentioning
confidence: 90%
“…However, further studies have indicated that IM30 is involved in maintaining the structure and stability of internal membranes in chloroplasts and cyanobacteria, similar to its bacterial homologue PspA, and thus has a more protective function 27,28 . In addition, IM30 has been found to enhance protein translocation via the chloroplast Tat pathway 29 and involvement in photosystem biogenesis has been suggested 21,[30][31][32] . Currently, no model combining these diverse IM30 functions has been proposed, and the exact role of IM30 remains enigmatic.…”
mentioning
confidence: 99%
“…Therefore, it has recently been suggested that VIPP1 is the major constituent of thylakoid centers [129]. Recent GFP-based live-cell imaging using confocal microscopy has revealed that, under low light conditions, VIPP1 is localized in a punctate manner preferentially at the cell periphery [53]. However, under high light levels, the number of punctate accumulations associated with internal thylakoid membranes increases substantially, suggesting a highly dynamic subcellular redistribution of VIPP1 under stress conditions (Chapter 21 [53,54]).…”
Section: Cytological Organization Of Thylakoid Biogenesismentioning
confidence: 99%
“…These include the VIPP1 protein, which is homologous to the bacterial phage shock protein PspA. VIPP1 has been implicated in thylakoid biogenesis and/or thylakoid maintenance in both cyanobacteria and chloroplasts [51][52][53]. The molecular details of VIPP1 functions are addressed in Chapter 21 [54] of this issue.…”
Section: Trafficking Of Lipidsmentioning
confidence: 99%